Creative leadership of Manager as managerial competence: value-oriented approach. Part I - V. N. Ivanov; E. V. Yakovleva (Омский научный вестник: Серия "Общество. История. Современность")
The two parts present the results of the study of the formation and development of creative leadership of the Manager as a managerial competence, which are relevant in modern conditions of active innovative transformations that increase the «demand» for innovation of labor collectives, measured by the effect of innovation. The purpose of the study to identify the fundamentally important and practically significant patterns of formation and development of creative leadership of the Manager as a managerial competence has determined the choice of value-oriented approach that allows a comprehensive description of the ongoing at all stages of the Manager and the surrounding society, internal and external processes aimed at innovation. In the first part of the article the substantiation of value-oriented approach to the formation and development of creative leadership of the Manager as a managerial competence is given, the possibilities of techniques and methods of approach to the study are revealed, which allowed to form a value-oriented model of creative leadership as a managerial competence, the concept aimed at the development of creative leadership, oriented to increase the effect of innovation in the industrial sector of the economy